Biobased Ionic Liquids as Multitalented Materials in Lipidic Drug Implants - Ana Júlio; Anaisa Sultane; Ana Silveira Viana; Joana Portugal Mota; Tânia Santos de Almeida (MDPI AG, 2021)
Lipidic implants are valuable controlled delivery systems that present good biocompatibility and are useful for long-lasting therapies. However, these promising systems can present inflexible drug release profiles that limit their performance. Thus, finding new materials to overcome this drawback is crucial. Herein, lipidic implants containing caffeine and poorly soluble salicylic acid and rutin were developed. The inclusion of Gelucire® 50/02, sucrose, and two biobased ionic liquids, [Cho][Phe] and [Cho][Glu], were evaluated as a mean to improve the performance of the systems. The formulation procedure, dye content distribution, drug content, drug release, water content, and lipidic erosion of the developed systems were assessed. AFM analysis of the implants containing ILs was also performed. The results demonstrated that neither Gelucire® 50/02 nor sucrose were suitable tools to improve the drug release profile. In contrast, the ILs proved to be promising materials for multiple reasons; not only did they facilitate the formulation and incorporation of the studied drugs into the implants, but they also allowed a more suitable release profile, with [Cho][Glu] allowing a higher drug release due to its ability to increase surface wrinkling. Hence, this study showcases ILs as multitalented materials in lipid-based drug implants.